Incorporating other substances as raw materials for fermented sugar in alcohol distilleries - Romel García-Prado; Amaury Pérez-Martínez; Karel Diéguez-Santana; Leyanis Mesa-Garriga; Inti González-Herrera; Meilyn González-Cortés; Erenio González-Suarez (Revista Facultad de Ingeniería Universidad de Antioquia, 2015)
This paper presents alternatives for meeting the deficit in sugared substrates in a territory with several sugar mills and ethanol distilleries so they can reach their current production capacity. By using secondary currents and diluted juices from the sugar production process, wastage was first reduced to 26.92%. Then by optimizing the molasses linking and bagasse between sugar mills and ethanol distilleries, an important problem was resolved allowing production capacity to be met. This represented a 154.96% increase over what was initially planned.